2006
DOI: 10.2175/106143006x99777
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydrophilic and Hydrophobic Microfiltration Membranes to Remove Microorganisms and Organic Pollutants from Primary Effluents

Abstract: Primary‐effluent wastewater from the Allegheny County Sanitary Authority (Pennsylvania) was used as a surrogate for combined‐sewer‐overflow waters contained in the sewershed. Pathogens contained in combined‐primary‐effluent wastewaters or combined‐sewer overflows (CSOs) may pose a human‐health threat to those coming in contact with such receiving waters. Polymeric ultra‐ and nano‐membranes can be used to capture these microorganisms from CSOs. This research investigates the ability of polymeric hydrophobic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…For an incompressible concentration layer the porosity and resistance are independent of the imposed pressure [21]. The value of rc can be estimated using the Carmen-Kozeny equation:…”
Section: Re = Re 8e (1 O)mentioning
confidence: 99%
See 1 more Smart Citation
“…For an incompressible concentration layer the porosity and resistance are independent of the imposed pressure [21]. The value of rc can be estimated using the Carmen-Kozeny equation:…”
Section: Re = Re 8e (1 O)mentioning
confidence: 99%
“…For a rigid spherical of average diameter, ap, the specific surface area is Sc = 6/ap, e c is the porosity of the concentration layer (for a randomly packed cake it is approximately 0.4) and the constant K is reported to have a value of 5.0 for laminar flow through the layer [21].…”
Section: Re = Re 8e (1 O)mentioning
confidence: 99%
“…This shows that POME can have both positive and negative effects on crop performance. POME has a high nutrient content, and large oil palm plantations prefer to use it directly as fertilizer (Modise et al, 2006). The application of palm oil mill effluent was reported to increase the growth of maize (Ogboi et al, 2010) while The growth and germination inhibitions of different vegetables after POME application to the soil was observed by Radziah (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have repeatedly shown that E. coli and C. perfringens are rejected by microfilters with pore sizes of 0.45 |im or less to an extent that those indicators are not detectable in the filtrate (Judd & Till 2000;Alonso et al 2001;Oota et al 2005;Modise et al 2006). A number of previous studies have also shown that microfiltration is effective at removing coliphage and other viruses from wastewater despite the small size of these particles (Winnen et al 1996;Alonso et al 2001;Oota et al 2005;Zheng et al 2005;Lv et al 2006;Zhang & Farahbakhsh 2007).…”
Section: Pathogen Counts In Micro-fíltered Samplesmentioning
confidence: 99%